MEMMANG SEBAGAI MANTRA PENGLARIS DAGANGAN KAJIAN TRADISI LISAN MASYARAKAT TANJUNGAN,PEMATANG SAWAH TANGGAMUS - Aulia Yunisa; Dea Yulianita; Mulyanto Widodo; Rahmat Prayogi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The development of the digital era has accelerated the dissemination of cultural information, including oral traditions, which are an important heritage of the Lampung people. One distinctive oral tradition that has received attention is memmang, a form of spell steeped in magical and spiritual values. This study aims to describe the existence of the memmang tradition in Lampung society, uncover its function and meaning, and preserve its preservation amidst the dynamics of modernization and globalization. The research method uses a qualitative descriptive approach with data collection techniques through interviews, observation, and document analysis, including traditional manuscripts as the primary source. The results show that memmang plays a central role in the social life and beliefs of the Lampung people, but is facing a decline in function due to changes in social values, religious influences, and minimal regeneration from the younger generation. Nevertheless, this tradition is still preserved to a limited extent by several communities through oral inheritance and written documentation. This study emphasizes the importance of documentation efforts, cultural education, and the use of digital technology so that the memmang oral tradition can continue to live and be relevant in the modern era.